Wild mushrooms - Carole Chauvin-Payan (Revue d'ethnoécologie)
This article presents the uses, consumption practices, and popular beliefs related to wild mushrooms in Europe and Siberia from the Neolithic period to the present day. First, we will introduce various saproxylic mushrooms used for starting fires, as well as the medicinal uses of some species. Then, we will describe the gathering and consumption practices of edible wild mushrooms in Europe and Siberia. These consumption practices, varying by culture, region, and time period, will be specified for six edible species. Finally, we will address popular beliefs and the magical-religious rituals associated with some mushroom species.